A reduced-order extended state observer–based trajectory tracking control for one-degree-of-freedom pneumatic manipulator. (April 2018) - Zhao, Ling; Liu, Xin; Wang, Tao; liu, Bo
In this article, a reduced-order extended state observer is proposed to deal with uncertainties and disturbances in tracking control for a one-degree-of-freedom manipulator pneumatic system. A tracking differentiator is designed to generate a smooth tracking signal and a corresponding differential signal of the reference input. A non-linear state error feedback is adopted to ensure the response rapidity and control precision. Furthermore, stability analysis of the proposed reduced-order extended state observer and the closed-loop system is also presented. Finally, the experimental results show the efficiency of the proposed scheme for the one-degree-of-freedom manipulator pneumatic system.